Analysis of Cognitive Abilities of Class VII Students in Physics Learning After The Application of The Model Advance Organizer Learning - Sibela, Suratmi; Rahman, Nurdin A.; Hamid, Fatma; Saprudin (Islamic Journal of Integrated Science Education (IJISE), 2024)
This study aims to determine the cognitive abilities of students on the concept of heat and its transfer in class VII SMP Negeri 5 Kota Ternate. This data collection uses reliability, distinguishing power and difficulty level test techniques. The test instrument used is a description question consisting of 8 questions of students' cognitive abilities. The data were analyzed quantitatively. The subjects of this study were students of class VII1 SMP Negeri 5 Kota Ternate as many as 26 students. From the overall cognitive results which include 3 indicators of students' cognitive abilities where students reach the sufficient category, namely in the pretest results of 15 students and postest 20 students with an average score of 41-60, because students are able to understand the problem and can explain appropriately in solving the problem, in the less category the pretest results of 8 students and postest 3 students with an average score of 21-40, while in the very poor category the pretest results of 2 students and 3 students with an average score of 0-20, because when answering questions students only focus on solving problems do not follow the stages in solving problems, students have not been trained to formulate problems by writing what is known and what is asked in the problem.